Interventions supporting medical practitioners in the provision of lactation care: A systematic review and narrative analysis - Melinda Boss; Nicole Saxby; Douglas Pritchard; Rafael Pérez‐Escamilla; Rhonda Clifford (Wiley, 2021)
Abstract Most children globally are not breastfed to recommendations. Medical practitioners are frequently visited in the first 6 months post‐partum, and the interaction at such visits significantly influences subsequent infant feeding decisions. Medical practitioners report that clinical practice in lactation is often disproportionately reliant on personal experience. This systematic review synthesises the literature on lactation health interventions used to support clinical decision making by medical practitioners. MEDLINE, Embase, PsycINFO, Scopus and Cochrane Library databases were searched for peer‐reviewed empirical studies published after 2000. Two reviewers independently screened and then assessed full‐text articles against inclusion criteria. Quality of reporting and risk of bias were independently assessed using three validated tools. No conclusions can be made regarding the success or failure of implementation strategies used or the outcomes of putting them into effect due to problems with study methodology, intervention reporting and risk of bias. Good‐quality research, which follows proven implementation frameworks, is needed to guide and sustain the incorporation of evidence‐based decision support into medical practitioners' care of breastfeeding mothers and infants.